Accounting for Water Insecurity in Domestic Water Demand Modeling. - Galaitsis, Stephanie. (2017)
Abstract: Future water planning efficacy depends upon the predictability of the systems under management. Water demand management uses price elasticity estimates to predict consumer demand in relation to water pricing changes, but studies have shown that many additional factors effect water consumption. Development scholars document the need for water security, however, much of the water security literature focuses on broad policies which can influence water demand. Previous domestic water demand studies have not considered how water security can affect a population's consumption behavior. This study is the first to model the influence of water insecurity on water demand. A subjective indicator scale measuring water insecurity among consumers in the Palestinian West Bank is developed and included as a variable to explore how perceptions of control, or lack thereof, impact consumption behavior and resulting estimates of price elasticity. A multivariate regression model demonstrates the significance of a water insecurity variable for data sets encompassing disparate water access. When accounting for insecurity, the R2 value improves and the marginal price a household is willing to pay becomes a significant predictor for the household quantity consumption. The model denotes that, with all other variables held constant, a household will buy more water when the users are more water insecure. Though the reasons behind this trend require further study, the findings suggest broad policy implications by demonstrating that water distribution practices in scarcity conditions can promote consumer welfare and efficient water use.; Thesis (M.S.)--Tufts University, 2013.; Submitted to the Dept. of Civil Engineering.; Advisor: Richard Vogel.; Committee: Richard Vogel, Annette Huber-Lee, and Elena Naumova.; Keywords: Water resources management, and Environmental engineering.